Evaluation of temperament in sheep of the 'Pampinta' breed and its influence on meat production (Semiárida, 2020)
Lambs losses represent profit damage in extensive sheep production. The aim of this work was to analyze the temperament expression of Pampinta sheep under different levels of interaction with humans and the relationship between it and maternal behavior and meat production. Two methods were used to evaluate the reactivity of the sheep: the Arena Test and a specific test to evaluate the maternal behavior score. The results obtained showed that the contact of the adult sheep with people did not moderate their reaction to the novel stimuli. It was also observed that the maternal behavior score and the individual production were not correlated with the temperament. It may be due to genetic factors of the breed and / or the methods used.Director: Zuccari, Abel Esteban - Co Director: Beierbach, Romina
Keywords: Reactivity; Maternal behavior; Mortality of lambs; Arena Test